(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: This study aims to assess the efficacy of mayo repair as a modality to treat small (less than 2 cm) paraumbilical hernias and to analyze the morbidity associated with the management. Methods: The study was conducted at Northwest General Hospital and Research Centre Peshawar with clinical features suggestive of Paraumbilical Hernia (70 diagnosed cases) from 1st March 2025 to August 2025. Pediatric age group and those patients requiring emergency surgery have been excluded. The following parameters were added: name, age, gender, residence, contact number, MR number, seroma and hematoma formation along with surgical site infections. The data was added to Microsoft Excell and transferred to SPSS version 23.0 for data analysis. The Pearson chi-square test was utilized to measure the correlation. Results are shown in the form of description, tables and charts. Results: In terms of post-operative outcomes, 16 (22.9%) patients had seroma formation, 7 (10%) patients had hematoma formation, and 13 (18.6%) patients had surgical site infections. It was noticed that the most common post-operative side effect of anatomical (mayo repair) was hematoma formation (p-value <0.05) and umbilical hernia repairs had the most favorable outcome regarding surgical site infections (p-value <0.05). Conclusions: Reconstruction of the abdominal wall in anatomical planes is an effective technique for treating small paraumbilical hernias despite having post-operative complications however this modality cannot be employed for larger defects.